Зарубежные традиции государственной миграционной политики как основа опыта построения региональных центров правовой грамотности для мигрантов - Medvedeva, Anastasiia (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2016)
This article is devoted to research on the regulations of foreigners’ adaptation to the conditions of legal reality in the Russian Federation. The author analyzes various approaches to the interpretation of the category of “migration” existing in Russian and foreign literature, as well as attempts to define state migration policy and identifies the factors affecting its shape. In addition, the pan-European legislation in the field of migration, in particular the basic legal acts is analyzed. The specifics of the implementation of migration policies of individual countries, including the current situation of migration in the region is revealed. During the research, the author's considers various migration programs, which received significant effects in foreign countries. As a result of generalization of foreign countries’ experience a proposal is put forward to establish a center of legal support for foreigners.